The Language Identities of Malaysians as Portrayed in Upin and Ipin (Sains Humanika, 2013)
Malaysian government has proposed the 1Malaysia concept as a means of maintaining the harmonious status in a multiracial country. Several efforts were done in realising the concept through media and one of it is through television animation series. The Upin and Ipin animation series is known to have successfully promoted Malaysian cultures and gained popularity for its vast moral contents, portraying Islamic values and educating Malaysians on the importance of harmonious relationships among people from different ethnic groups and religious backgrounds. This paper aims to discuss the language identities of Malaysians as portrayed in the animation series, of which the focus is on the linguistic elements. In this study, we conducted textual analysis, by which the language identities of the characters were analysed. Our data were 11 parts of the Upin and Ipin animation series that portrayed people from different ethnic groups interacting with each other. The findings show that the characters in the animation use different particles in representing their ethnicity. Besides that, a typical Malaysian speech pattern of the particle lah is found to be widely used by all Malaysians, regardless of their ethnic group. The first language interference, code switching and the act of accommodating a Chinese speech style are also discussed in light of Communication Accommodation Theory (CAT).
Keywords: Language identities; linguistic patterns; Communication Accommodation Theory (CAT); modal particles; L1 interference